An orchestration of the Sonata no. 3 in F-sharp minor, Op. 23 by Alexander Scriabin - De Castro Martins Amaro, Olga Maria (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MMus (Music))--University of Stellenbosch, 2009.